Morphology, mineralogy and rietveld texture analysis of ash deposits from a moving grate boiler. (15th April 2022) - Yongtie, Cai; Zhimin, Zheng; Zhenwei, Li; Anqi, Zhou; Wen, Wen; Lei, Luo; Wenming, Yang
Graphical abstract: (A) Sources of errors from synchrotron radiation; (B) Data reduction procedure by FIT2D; (C) Rietveld refinement procedure of texture analysis using MAUD for (C1) the standard sample and (C2) the investigated samples; (D) texture analysis by MTEX. ([53, 54, 120, 19, 50] ) Highlights: Application of synchrotron XRD and Rietveld analysis to determine mineral phases. Microstructure and texture analysis of mineral phases of the ash deposits. Mineral classification and transformation in the ash deposits. Summary of the procedures of synchrotron data treatment and texture analysis. Abstract: The release and transformation of inorganic species during combustion will cause severe ash-related issues, often leading to serious operational problems. To better understand these issues, several ash deposit samples collected from a biomass-fired moving grate boiler were characterized by inductively coupled plasma atomic emission spectroscopy, X-ray fluorescence, scanning electron microscope with energy dispersive spectroscopy and synchrotron radiation X-ray diffraction. The Rietveld refinement method was used to determine the mineral phases and texture information of ash deposits. The results showed that the fuel had a high slagging tendency and ash deposits were enriched in alkali and alkaline metal species. The petrology and morphology analysis indicated that they all presented layered structures and displayed heterogeneity in sizes and shapes with spherical, fibrous, prismatic and irregular morphologies and with the predominant surface compositions of O, Al, Si, Ca, Fe, K, Na and C. The Rietveld phase analysis of ash deposits demonstrated that several mineral types were identified, including oxides, silicates, phosphates, sulfides, sulfates and carbonates. The possible chemical reactions and mineral transformation during combustion were investigated. The texture exhibited in a sample can be classified as random, planar and fiber textures. The Rietveld texture analysis of minerals in the ash deposits showed that the texture indexes of most mineral phases were larger than one, indicating that the orientation distributions of these minerals were not random. Some of the pole figures of the minerals showed a weak orientation of densities, while some of them exhibited strong orientation of densities. Due to some peak overlaps existing between minerals, the texture of some mineral phases showed a fiber-like characteristic with several fiber components while some other minerals presented planar-like or biaxial-like texture.